A study comparing the practice of Australian maternity care providers in relation to maternal immunisation. (7th September 2018) - Krishnaswamy, Sushena; Wallace, Euan M.; Buttery, Jim; Giles, Michelle L.
Abstract : Background: Women's decisions regarding vaccination during pregnancy are heavily influenced by maternity care provider (MCP) recommendations. Understanding why MCPs may not recommend vaccination is central to improving vaccination rates. Aims: To examine the knowledge, attitudes and practice of Australian MCPs to maternal vaccination. Methods: We surveyed obstetricians, midwives and general practitioners (GPs) between September and November 2016. Providers were asked about their knowledge and current practice, and about their perceived roles in discussing and administering maternal vaccinations. Results: Eight hundred and seventy surveys were completed. Each MCP group believed they had the primary responsibility for discussing vaccinations but all groups perceived GPs as primarily responsible for administering vaccines. More midwives had concerns about safety (21/129, 16%) than obstetricians (9/359, 3%) and GPs (7/326, 2%) ( P < 0.001). Overall, 83% of MCPs recommended diphtheria‐tetanus‐acellular pertussis vaccination (dTpa) and 78% inactivated influenza vaccination (IIV) according to guidelines, with no differences between groups. Overall 77% provided dTpa onsite (GPs 99%, midwives 70%, obstetricians 60%, P < 0.001) and 71% provided IIV (GPs 99%, midwives 48%, obstetricians 54%, P < 0.001). Factors associated with recommending vaccination in accordance with guidelines and providing vaccination onsite were similar across groups: personal history of vaccination, confidence in vaccine knowledge, and awareness of recommendations for and belief in the safety of maternal dTpa. Conclusions: Among MCPs, the rates of recommending and providing maternal vaccination were higher than previously reported. Further improvements might be expected with increased awareness of guidelines, further education around vaccine safety, and by changing perceptions of the role of obstetricians and midwives in providing maternal vaccinations.